Microbially-induced calcite precipitation by ureolytic bacteria as agent for soil bio-stabilization method - Aliyu, Dardau Abdulaziz (2021)
Microbially-induced calcite precipitation (MICP) refers to the biochemical process of precipitating calcium carbonate (CaCO3) induced by bacterial urease activity with a complex microbial biochemical reaction occurring within the environment for the purpose of stabilizing loose soils. A loose soil poses great concern worldwide leading to severe environmental hazards such as building collapse, destruction of roads and railways, landslides, loss of lives and properties, with an estimated US$6 billion spent annually to finance over 40,000 soil improvement projects worldwide. This study is limited to calcite precipitation and bio-cementing effect of indigenous soil urease producing bacteria. The aim of this study is to explore the potential of indigenous urease producing bacteria towards soil stabilization. Isolation using CaCO3 precipitation media within 7 d to target highly active urease producing bacteria has successful isolated eight isolates (O6w, O42, O5w, O3a, O6a, O41, S73 and S70) from farmland soil samples at Ladang 15, Faculty of Agriculture, Universiti Putra Malaysia, Selangor, Malaysia. Farmland soils of Ladang 15 are known to be urea rich soil due to utilization of synthetic urea and organic manure as fertilizer for crop cultivation. Thus, favours distribution and diversity of urease producing bacteria. Phenotypic analysis indicates all isolates are Gram-positive, rod-shaped and produced circular colonies. The pH profile and growth profile of the isolates were studied and urease activity was measured by phenol hypochlorite assay method (O.D 626 nm) at 24 h interval for 120 h. The experimental results showed that all the isolates were able to sustain a steady growth up to 96 h, which later had produced significant precipitation of CaCO3. Among the eight isolates evaluated, isolate O6w and isolate O3a were selected based on the highest urease activity at 665 U/mL and 620 U/mL, respectively and able to increase and sustain alkaline culture condition (pH 8.71 ± 0.01 and 8.55 ± 0.01) which is suitable for CaCO3 precipitation. The isolates were identified based on 16S ribosomal RNA sequencing to be Bacillus cereus (O6w) and Bacillus paramycoides (O3a). An amount of 943 ± 57 mg/L and 793 ± 51 mg/L CaCO3 had been precipitated by B. cereus and B. paramycoides, respectively after 96 h of incubation. Studies on characterization of the precipitated CaCO3 crystals by scanning electron microscope (SEM) microanalysis have shown CaCO3 crystals of various sizes (2.0 μm - 23.0 μm) with different morphologies such as agglomerated rhomboids, cubic, flower-like and irregular shaped crystals. Confirmed by XRD indicated that precipitated CaCO3 is mostly calcite and a few aragonites. SEM micrographs on microstructural analysis of organic and sandy clay soils treated by both B. cereus and B. paramycoides have shown the formation of bio-precipitated CaCO3 deposited on soil particles (bio-cementing soil grains). Overall, observed experimental results attributed CaCO3 formation as a bacterial-associated process. Hence, the dynamic process of MICP leading to precipitation of CaCO3 is not chemically induced, but a microbially induced biochemical process directly linked with urea hydrolysis via urease activity. This study suggests that indigenous soil ureolytic bacteria with high urease activity are potentially useful as agent for soil bio-stabilization.